If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 4(x + 3) Reorder the terms: 17 = 4(3 + x) 17 = (3 * 4 + x * 4) 17 = (12 + 4x) Solving 17 = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 17 + -4x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 17 + -4x = 12 + 0 17 + -4x = 12 Add '-17' to each side of the equation. 17 + -17 + -4x = 12 + -17 Combine like terms: 17 + -17 = 0 0 + -4x = 12 + -17 -4x = 12 + -17 Combine like terms: 12 + -17 = -5 -4x = -5 Divide each side by '-4'. x = 1.25 Simplifying x = 1.25
| 11x=33x | | -x+9=29 | | 3x+7x-4=2 | | X-7.6=-6.9 | | 3t-t-4=t-4 | | 165=20-y | | cos(5x)=.5 | | x^2-rad(3x)-6=0 | | 8x+16-6x-12=2x+6 | | 11f+2(f+1)=5f-6 | | 2(x+60)-((x+50)+60)=210 | | 29x=29x | | 100=4x+3y+0.1z | | -4p+4(1+2p)=-38-3p | | x^4+3x^3+3x^2+3x=0 | | 5x^2+3x-2y^2-3y-1=0 | | -4-(13x+6)+17=2+x-(14x-5) | | -4-(13x+6)+17=2 | | 9(3n+2)=8(8n+1)+8 | | 0=8x^2-42x+45 | | 5x+7=12-x | | -5u^2+21u+20=0 | | 2(6a-1)-(2a-3)+3(7a-5)= | | -6(7x-6)+3=-42x+39 | | -3(1-2x)=15 | | 6x+9=12x-15 | | -6(7x-6)+3=42x+39 | | S(t)=5t^3-2t^2+9 | | 85y=12(7y+33) | | X^6+x^3-6x=0 | | 7(x-2)-3(2x-7)=6x+22 | | -6(x-3)-29=-11 |